A new modified incomprehensible but intelligible-in-time logics algorithm for modeling solid oxide fuel cell - Shahr Alshahr; Fatma A. Hashim; Ahmed Alshahir; Ahmed Fathy; Hegazy Rezk (Scientific Reports)
Abstract This work suggests a new modified incomprehensible but intelligible-in-time logics algorithm with random contraction strategy (RCS) in exploration phase in addition to new exploitation phase (REILA). The proposed REILA is employed to evaluate the best solid oxide fuel cell (SOFC) parameters in order to create its equivalent circuit. The REILA is an enhanced version of the classical algorithm designed to avoid falling in local solution and achieve well balance between exploration and exploitation phases. It is applied to solve twelve different functions of IEEE CEC’2022 test suite and compared with nine well-known algorithms. Then three famous constrained engineering problems (cantilever beam design, welded beam design, and speed reducer design) are applied to show the effectiveness of REILA in solving real world applications. The goal is to mitigate the sum mean squared error (SMSE) between the experimental and estimated curves. Two working scenarios of fuel cell are implemented: steady-state and dynamic-state. Both scenarios are examined under various operating situations. Comparison to reported approaches of interior search optimizer (ISO) and political optimizer (PO) is conducted. Also, new approaches of Aquila optimizer (AO), Chef-based optimization algorithm (CBOA), African vultures optimization approach (AVOA), gold rush optimizer (GRO), transient search optimizer (TSO), osprey optimization approach (OOA), and traditional ILA are programmed to assess the proposed strategy. The suggested method yielded a minimal fitness function of 1.5528e-06 for the steady-state model at 1173 K. The least error in the dynamic model found with the suggested REILA is 1.1267. The outcomes validated the methodology’s suitability, resilience, and proficiency in evaluating the parameters of SOFC equivalent circuit.